Hábitos alimentares e qualidade do sono em crianças de uma escola pública do município de Lavras-MG: efeitos da pandemia de COVID-19 - Hermes, Fernanda Nascimento (2021)
The social distancing imposed by the Covid-19 pandemic might have important impact in eating habits and sleep quality in child population. Objective: To evaluate the impact of the Covid-19 pandemic on sleep quality and eating habits of children in a public school of Lavras-MG. Methods: The study included a random sample of students of a public school of Lavras–MG, between 4 and 10 years old. The children and parents and/or guardians were evaluated in person before the pandemic beggining. During the pandemic, interviews were conducted by telephone calls. Anthropometric measurements of weight, height, body mass index (BMI) and waist circumference measurement were performed to characterize the sample only at the beginning of the study. The meals offered by school was also analyzed before the pandemic. The sleep quality was assessed through the Children's Sleep Habits Questionnaire (QSTC-PT) and food intake by a 24-hour recall (R24h). Regarding the statistical analysis test t of samples matched for the quantitative variables and chi-square and Mcneman tests for analysis of qualitative variables. The level of significance adopted was p<0.05. Results: The sample consisted of 37 children with a mean age of 7.38±1,156 years, 62.2% of them were male and nutritional status was classified as eutrophy in 65.4% of the participants. The school menu offered before de pandemic was evaluated as “poor” in the most of the evaluated parameters. Regarding the changes caused by the Covid-19 pandemic, 43.2% of the parents reported changes in the family income with an increase in the "D" and "E" socialeconomic levels. There was an increase in total sleep time and a reduction in the overall mean QSTC score, this reduction was also significant in the categories "difficulty waking up in the morning' and "daytime sleepiness". In food intake, a reduction was observed in the number of meals. Final considerations: It can be concluded that the Covid-19 pandemic has already resulted in a reduction in monthly family income, increased total sleep time and improved sleep quality in children in addition to reduction in the number of meals and loss of school meals.